Empirical Assessment of Selected Financial Indicators and Nigeria Gross Domestic Product - Acha, Chigozie Kelechi; Umezurike, Chinaegbomkpa (Universitas Negeri Malang, 2018)
This study undertook an overview of the financial sector and considered the contributions of some selected financial indicators to the gross domestic product (GDP) in Nigeria. Data were obtained from the statistical bulletin of the Central Bank of Nigeria (CBN) for the period, 1990-2016. The variables considered include: Lending rate (LR), Real Interest rate (RIR), Money Supply (M2), Credit to Private Sector (CPS), Inflation rate (IR). Multiple regression analysis method was used to analyze the data. From the analysis, it is observed that credit to private sector (CPS) has a positive relationship with the GDP whereas the rest had negative relationship with the GDP. Further analysis using analysis of variance (ANOVA) showed that one of the factors (CPS) is significant. From the result obtained, it is recommended that the private sector should be given more access to credit. This will help in improving the economy since it has shown to have a positive relationship with the GDP.Keywords: Inflation; Lending rate; Money supply; Gross Domestic ProductJEL Codes: E43, E60, O40